2004
DOI: 10.1086/381055
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of CERKL, a Novel Human Ceramide Kinase Gene, Causes Autosomal Recessive Retinitis Pigmentosa (RP26)

Abstract: Retinitis pigmentosa (RP), the main cause of adult blindness, is a genetically heterogeneous disorder characterized by progressive loss of photoreceptors through apoptosis. Up to now, 39 genes and loci have been implicated in nonsyndromic RP, yet the genetic bases of >50% of the cases, particularly of the recessive forms, remain unknown. Previous linkage analysis in a Spanish consanguineous family allowed us to define a novel autosomal recessive RP (arRP) locus, RP26, within an 11-cM interval (17.4 Mb) on 2q31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
157
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(160 citation statements)
references
References 21 publications
3
157
0
Order By: Relevance
“…Recent clinical studies have identified mutations in the human ceramide kinase like (CERKL) gene in patients with autosomal recessive retinitis pigmentosa (33). No CERKL homolog has been identified in the Drosophila genome.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical studies have identified mutations in the human ceramide kinase like (CERKL) gene in patients with autosomal recessive retinitis pigmentosa (33). No CERKL homolog has been identified in the Drosophila genome.…”
Section: Discussionmentioning
confidence: 99%
“…This region consists entirely of RP26/ CERKL gene sequence, indicating that this gene was also directly disrupted. A recessive nonsense mutation in the RP26/CERKL gene has been described in two unrelated Spanish families with retinitis pigmentosa, 32 indicating that disruption and the resulting haploinsufficiency of this gene is unlikely to explain the clinical phenotype of the patient. The direct gene disruptions of the PKNOX2/PREP2 and RP26/CERKL genes are not discussed further in this paper.…”
Section: Characterization Of Loci Affected By the Karyotype Rearrangementioning
confidence: 99%
“…1-3 CRD can manifest under a variety of inheritance models, though the autosomal recessive mode of inheritance is the most prevalent. To date, eight genes responsible for autosomal recessive CRD have been identified: ABCA4 (OMIM#601691), 4 ADAM9 (OMIM#602713), 5 C8orf37 (OMIM#614477), 6 CERKL (OMIM#608381), 7 EYS (OMIM#612424), 8 RPGRIP1 (OMIM#605446), 9 RAB28 (OMIM#612994) 10 and TULP1 (OMIM#602280). 11 However, the known variants do not account for all cases of CRD.…”
Section: Introductionmentioning
confidence: 99%